2016
DOI: 10.1016/j.jpainsymman.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Cytokine Genes Are Associated With Higher Levels of Fatigue and Lower Levels of Energy in Women After Breast Cancer Surgery

Abstract: Context Little is known about the phenotypic and molecular characteristics associated with changes over time in fatigue and lack of energy in patients with breast cancer. Objectives To identify subgroups (i.e., latent classes) of women with distinct fatigue and energy trajectories; evaluate for differences in phenotypic characteristics between the latent classes for fatigue and energy; and evaluate for associations between polymorphisms in genes for pro- and anti-inflammatory cytokines, their receptors, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 88 publications
3
46
0
Order By: Relevance
“…Only three studies used LPA to identify groups of oncology patients undergoing CTX with distinct fatigue profiles. [12,19,20] In the two studies that used average fatigue scores,[19,20] Higher and Lower Fatigue classes were identified. In both studies, patients in the Higher Fatigue class were significantly younger and reported lower levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies used LPA to identify groups of oncology patients undergoing CTX with distinct fatigue profiles. [12,19,20] In the two studies that used average fatigue scores,[19,20] Higher and Lower Fatigue classes were identified. In both studies, patients in the Higher Fatigue class were significantly younger and reported lower levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients heterozygous or homozygous for IL1R1 (rs2110726) rare variants had decreased odds of belonging to the "lower energy" group. To this point, the results of the Genetic polymorphisms associated with common symptoms experienced by breast cancer patients association between IL1B (rs16944) and the development of fatigue remain contradictory where a study [54] reported increased while the other [59] reported decreased likelihood of belonging to the fatigued group in patients carrying the rare variant allele while two other studies reported no significant association [60,61].…”
Section: Cytokine Genes and Fatigue And Energymentioning
confidence: 99%
“…A number of Single Nucleotide Polymorphisms (SNPs) in proinflammatory cytokines have been reported to be linked with breast cancer susceptibility and prognosis [44][45][46][47][48] as well as the development of treatment-related adverse effects [49,50]. Some evidences have emerged from recent literatures that the energy level in an individual may be considered as a distinct but related symptom to fatigue [51][52][53][54]. Therefore, owing to the relationship between fatigue and energy level, it is hypothesized that a significant number of cytokines and neurotransmitters [55][56][57][58] could play a vital role in the development of these related symptoms.…”
Section: Fatigue and Energy Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers recently found that in patients followed for 6 months postsurgery for breast cancer, those with the IL1B SNP rs16944 (the number following “rs” is the reference sequence number identifying the specific SNP) with two A alleles (genotype AA) had a 2.98-fold higher risk of belonging to the “higher fatigue” class in their analysis. The phenotypic characteristics of this class included younger age, lower Karnofsky Performance Status score, higher self-administered Comorbidity Questionnaire score, higher fatigue score at study enrollment and higher number of lymph nodes removed (Kober, Smoot, et al, 2016). …”
Section: Utilization Of Genotype–phenotype Associations In Clinical Pmentioning
confidence: 99%